Analyzing Iran's Legislative Criminal Policy in Dealing with Environmental Terrorism, Emphasizing the Need for Criminalization and Preventive Measures - behrouz sepehri; Nourooz Kargari; mohammad ashouri; ghassem ghassemi (محیط زیست و توسعه فرابخشی)
Introduction: environmental security, is a necessary condition for the health and continuity of human life on earth and due to the vital, widespread and inevitable dependence of humans on the environment, if the environmental security is taken away and it is removed from the possibility of healthy living, as a result of the goal or the means of placing the environment, following environmental terrorism, with various methods such as polluting the natural and man-made environment with dangerous substances, extensive and irreparable damage is caused to human life and health And often, the most obvious effects of damage to the safety and health of the environment appear in the form of epidemics, and on the other hand, the cross-border effects of such actions and the possibility of transferring the said effects from through the flow of air or water or the carriers of disease agents to countries and regions beyond the place of the accident, and the possibility of spreading some of these effects on the life and health of future generations, reveals the seriousness of the danger of environmental terrorism, hence, The purpose of this thesis is to explain the vital necessity of legal, technical and specialized contrast, against environmental terrorism in the form of an efficient criminal policy with international interaction, with emphasizing the extent and irreparability of the effects caused by environmental terrorism, and the necessity and importance of preventive measures.Materials and Methods:  In terms of the goal, the current research will cause expansion the legal theories and doctrine and complete the previous theories with the fundamental method of the research results, and also with the practical approach, effective practical solutions to deal with environmental terrorism will be presented, and on the other hand, the materials and information used in the research, They are collected with the library method and after collecting and categorizing the materials and information, with the descriptive-analytical method, the findings and the collected materials are analyzed logically and legally and they are used as the basis of citation to strengthen the approach of the researcher in the relevant subject.Results: In a comprehensive and efficient criminal policy to contrast against environmental terrorism, in addition to criminalizing this criminal phenomenon along with the real conceptology and in addition to recognizing its specific elements, it is expected that with the necessary criminal measures, specialized measures will be taken to identify and criminalize behaviors that it has a preliminary aspect to dangerous crimes, and it is possible that environmental terrorism is also committed through them, and therefore, in order to prevent this criminal phenomenon, criminalize such behaviors in the form of obstruction crimes seems necessary.Discussion: In Iran's criminal system, environmental terrorism has not been considered as an independent criminal behavior, with specific elements and specific conditions, However, due to the inherent of the behaviors related to environmental terrorism, this type of terrorism is inherently reprehensible, and as a rule, it can be included in various legal elements in the criminal laws, and on the other hand, due to the analogy of some elements of this criminal phenomenon with the destruction of the earth, According to jurisprudence, significant examples of environmental terrorism behaviors can be considered as examples of corruption in the land subject to Article 286 of the Islamic Penal Code (approved in 2012). However, in the set of regulations in various fields, some deterrent criminal contrivances are visible in the form of obstruction crimes, which are effective in the process of preventing environmental terrorism and play an effective role in the effectiveness of the criminal policy of counteraction.